PERBEDAAN INFORMASI CITRA ANATOMI MRI PELVIS SEKUENS T1 WEIGHTED POTONGAN SAGITAL PADA KASUS KANKER SERVIKS DENGAN VARIASI SUPRESSION LEVEL SPECTRAL ADIABATIC INVERSION RECOVERY (SPAIR) - Fitri Puspita Dewi; Luthfi Rusyadi; Sudiyono (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background : MRI Pelvic examination with cervical cancer case using the fat suppression SPAIR method to suppress fat to get an optimal picture. In SPAIR, there are three variations of fat suppression namely Strong Supression Level, SPAIR Supression Level Medium and SPAIR Supression Level Weak. At the Radiology Installation at Saiful Anwar Malang Hospital, the pelvic MRI examination used a weak SPAIR sequence while Dr. Sardjito uses strong SPAIR. This study aims to determine differences in information on pelvic MRI anatomical images and to find out better information on anatomical images on MRI pelvis T1 weighted sagittal sequences in cervical cancer cases with variations in Supression Level Spectral Adiabatic Inversion Recovery (SPAIR) Methods : The research used quantitative research method with experimental approach where is done in Radiology Installation of Dr. Sardjito Hospital Yogyakarta. The date were collected by examining MRI Pelvic with cervical cancer cases in 6 patients. Then scanning isdone on the sagittal piece with SPAIR Strong T1 Sequence, SPAIR Mediumand SPAIR Weak. Presented to three radiologist doctors of assess. Once the image judged by the three respondents, the the assessment results are summarized and then in a statistical test using SPSS version 16.0 with the method of friedman. Results : The result showed that there were significant diference of anatomical information between the SPAIR Strong, SPAIR Medium and SPAIR Weak on the MRI pelvic exmination of the sagittal cut in case of cervical cancer with p-value 0.003 (p<0.005). the SPAIR Weak variation has better anatomical information in MRI Pelvic examination of the sagittal cut in case of cervical cancer with Mean Rank value of SPAIR Weak variation 3.00, followed by SPAIR Strong sequence with value 1.92 and low SPAIR Medium sequence with value 1.08. Conclusion : Significant values ​​were obtained with p value = 0.003 (p <0.05) which means that there is information on anatomical information on MRI pelvis T1 weighted sagittal sequences in cervical cancer cases with the Spectral Adiabatic Inversion Recovery (SPAIR) Level suppression. Information on better anatomical images on MRI pelvis T1 weighted sagittal sequences in cervical cancer cases with the most optimal variation of Adiabatic Inversion Revovery (SPAIR) Suppression, namely weak SPAIR with mean rank of 3.00. Keywords : SPAIR, Cervices Cancer, MRI Pelvi